Platoon leader - McDonough, James R., 1946- (Novato, CA : Presidio, 1985)
A remarkable memoir of small-unit leadership and the coming of age of a young soldier in combat in Vietnam.
August 1, 1971: LZ English -- The road to war -- Welcome to Vietnam -- 2d platoon -- Taking charge -- The wounding -- Brief interlude -- If at first you don't succeed... -- A cast of characters -- Prelude to a fight -- Battle -- Aftermath -- The lowly infantryman -- The rains come -- American ingenuity -- The enemy builds strength -- A day at the beach -- Thanksgiving -- "Just like you and me" -- The order -- The patrol back -- Night movement -- End of a mission.
Keywords: McDonough, James R., -- 1946-; United States. -- Army -- Officers -- Biography; 1961 - 1975; Vietnam War, 1961-1975 -- Personal narratives, American; Command of troops; Soldiers -- United States -- Biography; Soldiers; United States; Biography; Personal narratives, American; Autobiographies; Biographies; Personal narratives -- American; Biographies; Personal narratives, American; Autobiographies; Biographies